Antimicrobial resistance of clinical bacterial isolates according to the WHO’s AWaRe and the ECDC-MDR classifications: the pattern in Ghana’s Bono East Region - Walana, Williams; Vicar, Ezekiel Kofi; Kuugbee, Eugene Dogkotenge; Sakida, Francis; Yabasin, Iddrisu Baba; Faakuu, Eric; Amfoabegyi, Solomon; Ziem, Juventus Benogle (Frontiers in Antibiotics, 2023)
Introduction Antimicrobial resistance (AMR) remains a significant health challenge globally and nations have the responsibility to maintain a constant surveillance of AMR, particularly for the emergence of multidrug-resistant (MDR) isolates to existing antibiotics. Against this backdrop, we applied the WHO’s AWaRe (ACCESS, WATCH, and RESERVE) antibiotics classification and the European Centre for Disease Prevention and Control (ECDC)’s multidrug resistance definition for AMR isolates from clinical specimens. Method This study reviewed bacterial culture and antibiotic sensitivity test outcomes. These results were then grouped according to the AWaRe and ECDC-MDR classifications. Results In all, the culture and sensitivity results of the 3,178 clinical specimens were investigated, of which 59.5% were from female patients. The pathogens were isolated from 1,187 specimens (37.4%). The WHO’s ACCESS antibiotics, tetracycline, showed a relatively high level of insusceptibility, particularly among Gram-positive (GP) isolates (ranging from 66.7% to 76.7%), along with augmentin (ranging from 44.7% to 81.3%) and cloxacillin (ranging from 50.0% to 78.1%). However, the Gram-negative (GN) isolates showed a relatively high level of susceptibility to amikacin, augmentin, and nitrofurantoin. The WHO’s WATCH antibiotics, cefuroxime, ceftriaxone, cefotaxime, and ciprofloxacin showed a relatively high level of non-responsiveness among the GN isolates, particularly Proteus (ranging from 31.4% to 78.4%), Pseudomonas (ranging from 21.4% to 96.4%), and Enterobacter (ranging from 62.5% to 100%) spp. Among the WHO’s RESERVE antibiotics, resistance to ceftazidime was commonly associated with the GN coliform isolates: Eschericha coli, Klebsiella, and Citrobacter spp. Insusceptibility to meropenem was frequently observed in Staphylococcus spp., E. coli, coliforms, and Proteus spp. Out of the 1,187 isolates, 15.5% (184) were GAT (gentamycin, ampicillin, and tetracycline) MDR, of which 61% (112/184) were from specimens of female patients. The most predominant GAT-MDR isolates were Staphylococcus spp., E. coli, coliforms, and Klebsiella spp. Conclusion In conclusion, the study revealed a relatively high level and diverse range of AMR. However, MDR in accordance with the ECDC definition was relatively low. There is, therefore, a need to have further research on AMR to inform national criteria for MDR in Ghana.